Adeno-associated virus packaged TRPC5 gene therapy alleviated spinal cord ischemic reperfusion injury in rats. Issue 1 (8th January 2020) - Shen, Nana; Wang, Lin; Wu, Yiling; Liu, Yanlin; Pei, Haitao; Xiang, Hongfei
Abstract : Spinal cord injury (SCI) is a devastating disease with few effective treatments. This study mainly explored the mechanism of TRPC5 gene in the treatment of spinal cord ischemia reperfusion injury from the perspective of angiogenesis. Western blot, immunohistochemistry, hematoxylin and eosin, ELISA, and reverse transcription-PCR (RT-PCR) were used to detect the expression levels of related angiogenic proteins such as von Willebrend factor (vWF), vascular endothelial growth factor (VEGF), CD31, and HIF-1α. The results showed that compared with the IR group, the Basso, Beattie, and Bresnahan scores of IR + adeno-associated virus (AAV) + TRPC5 group were higher with significant difference. And compared with ischemia/reperfusion (I/R) group, RT-PCR and ELISA results showed that inflammatory factors such as IL-6, IL-1β, and TNF-α were significantly reduced in IR + AAV + TRPC5 group. In addition, the expression of vascular related proteins such as vWF, VEGF, and CD31 in spinal cord tissue were all increased. Taken together the results, we suggest that TRPC5 could significantly increase the expression of angiogenic protein and slow down the occurrence of inflammatory response to repair the SCI.